[2.2]Paracyclophane–Triazolyl Monophosphane Ligands: Synthesis and Their Copper and Palladium Complexes. Issue 9 (13th February 2013) - Austeri, Martina; Enders, Mirja; Nieger, Martin; Bräse, Stefan
Abstract: Triazole‐based phosphanes have recently been shown to be interesting ligands in organometallic catalysis. The synthesis of novel [2.2]paracyclophane‐substituted triazole‐based phosphane ligands was achieved. The possibility to synthesize these molecules in a highly enantioenriched form is also reported. Moreover, the ability of the novel ligands to coordinate with metal centers was explored. Besides a dinuclear copper complex, a Pd II complex could also be isolated, the structure of which was characterized by X‐ray analysis. Pd II complexes derived from these ligands provide highly active catalysts for the Suzuki–Miyaura coupling of aryl chlorides. Abstract : Novel triazole‐based phosphane ligands were obtained from ethynyl‐ or azido[2.2]paracyclophane through a modular approach. Their coordination to metals was explored, and a Pd II complex was characterized by X‐ray analysis. Application of these ClickPhos ligands in the Pd‐catalyzed Suzuki–Miyaura coupling of aryl chlorides is also reported.